2021
DOI: 10.3389/fphys.2021.636997
|View full text |Cite
|
Sign up to set email alerts
|

The Thermoregulatory and Thermal Responses of Individuals With a Spinal Cord Injury During Exercise, Acclimation and by Using Cooling Strategies–A Systematic Review

Abstract: Background: In individuals with a spinal cord injury thermoregulatory mechanisms are fully or partially interrupted. This could lead to exercise-induced hyperthermia in temperate conditions which can be even more distinct in hot conditions. Hyperthermia has been suggested to impair physiological mechanisms in athletes, which could negatively influence physical performance and subjective well-being or cause mild to severe health issues.Objective: The aim was to evaluate the literature on the thermoregulatory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 73 publications
1
39
0
Order By: Relevance
“…In AB, it was observed that hot environmental conditions seem to influence the activity patterns (i.e., reduced high-intensity activity, total distance) [20]. As a result of the loss of vasomotor control and the absence of sweating response below the lesion level in individuals with a SCI (the sympathetic innervation of the eccrine sweat glands exits the spinal cord at T1-L2) [30,31], it has to be noted that the impairment of the thermal and thermoregulatory responses depends on the level of the lesion and the completeness of the spinal rupture [13]. Therefore, it can be expected that the performance of players with a low-level lesion would not be affected by the same amount as in cases of athletes with a high-level lesion.…”
Section: Comparison Of Hot and Tmpmentioning
confidence: 99%
See 4 more Smart Citations
“…In AB, it was observed that hot environmental conditions seem to influence the activity patterns (i.e., reduced high-intensity activity, total distance) [20]. As a result of the loss of vasomotor control and the absence of sweating response below the lesion level in individuals with a SCI (the sympathetic innervation of the eccrine sweat glands exits the spinal cord at T1-L2) [30,31], it has to be noted that the impairment of the thermal and thermoregulatory responses depends on the level of the lesion and the completeness of the spinal rupture [13]. Therefore, it can be expected that the performance of players with a low-level lesion would not be affected by the same amount as in cases of athletes with a high-level lesion.…”
Section: Comparison Of Hot and Tmpmentioning
confidence: 99%
“…It can be argued that low lesion level players with a lesion below T6 are able to thermoregulate their body similar to AB. Players with a high lesion level (i.e., above T6) are associated with considerably worse thermoregulation [13]. Hence, it makes sense to take a closer look at players with a lesion level above and below T6 (Tables 4 and 5).…”
Section: Comparison Of Hot and Tmpmentioning
confidence: 99%
See 3 more Smart Citations